2019
DOI: 10.1021/acsmacrolett.8b00924
|View full text |Cite
|
Sign up to set email alerts
|

Complexation of a Conjugated Polyelectrolyte and Impact on Optoelectronic Properties

Abstract: Electrostatic assembly of conjugated polyelectrolytes, which combine a π-conjugated polymer backbone with pendant ionic groups, offer an opportunity for tuning materials properties and a new route for formulating concentrated inks for printable electronics. Complex coacervation, a liquid–liquid phase separation upon complexation of oppositely charged polyelectrolytes in solution, is used to form dense suspensions of π-conjugated material. A model system of a cationic conjugated polyelectrolyte poly­(3-[6′-{N-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
94
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(101 citation statements)
references
References 65 publications
6
94
1
Order By: Relevance
“…Poly[3-(6'-bromohexyl)thiophene] (P3BrHT) was synthesized according to previous literature. 61,62 An oven-dried Schlenk flask containing 2,5 dibromo-3-(6-bromohexyl)thiophene was placed under vacuum for 2 hours. Dry, degassed THF was added via syringe and the mixture was sparged with Nitrogen.…”
Section: Synthetic Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Poly[3-(6'-bromohexyl)thiophene] (P3BrHT) was synthesized according to previous literature. 61,62 An oven-dried Schlenk flask containing 2,5 dibromo-3-(6-bromohexyl)thiophene was placed under vacuum for 2 hours. Dry, degassed THF was added via syringe and the mixture was sparged with Nitrogen.…”
Section: Synthetic Methodsmentioning
confidence: 99%
“…59,60 Large, polarizable ionic side-chain moieties serve to weaken ionic associations and increase ion dynamics without the presence of solvent, while the conjugated backbone imparts electron conductivity. 61,62 Polythiophenes with imidazolium side chains have shown intrinsic ionic conductivity up to 10 -4 S cm -1 in the neat state, while also showing evidence of significant long-range order in scattering studies. 60,63 While Ionic liquid functionalized conjugated polymers show potential as solvent-free mixed ion and electron conductors, to this point there have been few studies that investigate lithium-ion conduction in ionic liquid functionalized conjugated polymers.…”
Section: Introductionmentioning
confidence: 99%
“…Work by Danielsen et al demonstrated the ability to form liquid coacervates through the use of cosolvent mixtures. 278 Beyond the novelty of invoking π-π interactions, coacervates of conjugated polymers are particularly interesting because of their optical properties. In particular, the formation of a polyelectrolyte com-plex has been shown to result in an increased π-conjugation length, enhanced emissivity, and a dramatically increased fluorescence quantum yield.…”
Section: Conjugated Polymersmentioning
confidence: 99%
“…This is particularly important as the dilute branch is ignored or constrained to have zero polymer in most theories and simulations of coacervation; yet, the dilute branch is important for both fundamental studies and industrial applications as coacervates are often prepared by entering the phase coexistence window from dilute conditions. 20,22 A single valence of small ions is chosen rather than the total salt concentration (ρs) or the ionic strength, I = ∑ i=± q 2 i ρi to highlight the importance of charge neutrality and partitioning with asymmetries, discussed in Secs. III C-III E. Counter-ions of the polyampholyte are included in ρs (and thus in the ρs,− axis).…”
Section: B Excess Saltmentioning
confidence: 99%
“…Both simple and complex coacervates, ubiquitous throughout nature from membraneless organelles [1][2][3][4][5][6][7][8][9][10][11] to the wet-adhesion [12][13][14] of mussels and sandcastle worms, have found numerous applications in the food industry, [15][16][17] drug delivery, [18][19][20][21] and organic electronics. 22 Simple, single-component, or self-coacervation of polyampholytes and complex coacervation in the case of mixtures of oppositely charged polyelectrolytes arise from liquid-liquid phase separations that produce a polymer-rich coacervate in coexistence with a polymer-depleted supernatant comprised of primarily salt ions in solution. The broad interest in applications and their fundamental polymer physics has spurred parameterization of their structures and phase diagrams [23][24][25][26][27][28][29][30][31] as well as numerous theories for predicting the richness of coacervation phenomena.…”
Section: Introductionmentioning
confidence: 99%